The Dative : Volume 2: Theoretical and contrastive studies. - Van Langendonck, Willy (John Benjamins Pub. Co., 1998)
This book is the second part of a two-volume reader on the 'Dative'. In the first part, which appeared in 1996, eleven papers were presented providing a syntactic and semantic description of the category 'Dative' in eleven languages. The aim of this second part is to discuss several aspects of the Dative in greater detail. It contains eight papers dealing with theoretical considerations on 'dativity' as well as with contrastive, typological and diachronic issues. A major concern is the relation between form (case, grammatical relation) and meaning (semantic roles or other kinds of meaning). Mo.